2016
DOI: 10.5539/jsd.v9n3p208
|View full text |Cite
|
Sign up to set email alerts
|

Are Australian Aboriginal Communities Adapting to a Warmer Climate? A Study of Communities Living in Semi-Arid Australia

Abstract: Communities around the world adapt to warming climates in a number of ways. Adaptations can often be energy intensive or dependent on expensive infrastructure to cope with harsh weather, so the use of renewable energy and energy efficient housing is becoming an increasing feature in conversations about climate change adaptation. The cost of energy for households continues to increase, with this cost adding considerable financial pressure on low-income households in both developed and developing countries. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Meanwhile, the prevalence of over‐crowding in Aboriginal housing in the Northern Territory is well established (see, for example, Lea & Pholeros, 2010; Stevens & Bailie, 2012). Functioning as the service centre for many remote communities in the region, Alice Springs is an unsurprising site of transience (Horne et al, 2013; Race et al, 2016; Taylor, 2013). Further, a recent study with women residing in town camps reported that frequent ‘visitors' were regarded as a major safety issue for women and children (Brown, 2019).…”
Section: ‘Breaking the Cycle’ And Youth As A Problemmentioning
confidence: 99%
“…Meanwhile, the prevalence of over‐crowding in Aboriginal housing in the Northern Territory is well established (see, for example, Lea & Pholeros, 2010; Stevens & Bailie, 2012). Functioning as the service centre for many remote communities in the region, Alice Springs is an unsurprising site of transience (Horne et al, 2013; Race et al, 2016; Taylor, 2013). Further, a recent study with women residing in town camps reported that frequent ‘visitors' were regarded as a major safety issue for women and children (Brown, 2019).…”
Section: ‘Breaking the Cycle’ And Youth As A Problemmentioning
confidence: 99%
“…The residents of indigenous communities have strong social networks, a close relationship with their land, and considerable family and kinship responsibilities [36]. Previous studies have indicated that traditional ecological knowledge practices and cultural and social relationships should also be seen as critical components to the relocation and adaption of indigenous people's [37].…”
Section: Sustainability Perceptionsmentioning
confidence: 99%
“…liveability more generally (e.g. Race et al 2016aRace et al , 2016b. These issues are neatly summarised by Howden (2017) in his John Milne Memorial Rangeland Journal Lecture at the 2017 ARS Biennial Conference.…”
Section: Climate and Environmental Changementioning
confidence: 99%